The new EU regulations for food safety (Italian Journal of Public Health, 2007)
The inspirational principles of the norms known as the “Hygiene package”: the framework of new perspectives on food safety. At the beginning of the 1980s, all member states of the World Trade Organisation (WTO) subscribed to international agreements regarding strategies for food production and its marketing. These agreements, known as TRIPS (Agreement on Trade- Related Aspects of Intellectual Property Rights), GATT (General Agreement on Tariffs and Trade), GATS (General Agreement on Trade in Services) and TRIMS (Agreement on Trade-Related Investment Measures) [1] signalled the beginning of a new, globalized, commercial strategy on food products which has also caused importantrepercussions within the European boundaries, but with some fundamental differences.
Keywords: Safety; quality; hygiene; harmonisation; food; nourishment